A New Addition to the King James Family - Eldridge, Michael D. (The expository times, 2003)
Reviews the English Standard Version (ESV) of the King James translation of the Holy Bible. Weaknesses of the New International Version; Analysis of Mark's Gospel as rendered by the ESV; Policy regarding gender-inclusive language.